Co by bylo, gdyby... : historie alternatywne z Henrykiem Samsonowiczem, Januszem Tazbirem, Jerzym Skowronkiem, Andrzejem Ajnenkielem - Samsonowicz, Henryk; Tazbir, Janusz; Skowronki, Jerzy; Ajnenkiel, Andrzej; Osica, Janusz; Sowa, Andrzej (Warszawa : Dom Wydawniczy Bellona, 1998)
Conversations with noted Polish historians who voice their opinions about events in Polish history which would have been different if alternative events had happened.
Keywords: Poland -- History